Pengembangan Media Pembelajaran Games Based Learning Menggunakan Wordwall Berbasis PjBL untuk Mendukung Kemampuan Kreativitas Siswa Pada Materi Sistem Koloid: Penelitian - Bina Nurani Sibarani; Afrida; Febbry Romundza (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aimed to develop and analyze the feasibility of a games-based learning medium based on Project-Based Learning (PjBL) using Wordwall with Google Sites to enhance students' creativity in colloidal system material. This study adapted Lee & Owens' Research and Development (R&D) model, comprising analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, observations, and questionnaires administered to material experts, media experts, chemistry teachers, and 10 eleventh-grade Phase F students at Nommensen High School Jambi City. The research results indicated that the developed learning medium achieved a "Very Feasible" category based on material expert validation (average score 4.4) and media expert validation (average score 4.5). The chemistry teacher's assessment also classified this medium as "Very Feasible," with an average score of 4.7. Student responses to the medium were highly positive, reaching a percentage of 88,9% in the "Very Good" category. These findings suggest that the games-based learning medium based on PjBL with Google Sites is highly feasible and effective in facilitating the understanding of colloidal material and fostering student creativity.